1963
DOI: 10.1104/pp.38.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrol of Anthocyanin Synthesis in Milo Seedlings

Abstract: Prolonged irradiation at moderately high intensities is a requirement for anthocyanin synthesis in many plants. Action spectra for anthocyanin formation, however, are different for nearly every species examined (1,5,6,7,9). In general, a maximum is present between 400 and 500 mg (blue) or one between 400 and 500 m, and another between 600 and 800 myi (blue & red). In some species a second controlling photoreaction which requires brief irradiances at relatively low intensities is present (1, 6). The latter exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
73
2
3

Year Published

1964
1964
1989
1989

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 7 publications
8
73
2
3
Order By: Relevance
“…The internal concentration at the site of action is n'ot known, but it is probably less than in the external solution. Factors of penetration and problems of degradation could also account for the higher concentrations required (26 (4,20) others implicate one of them in a role in gene activation (9). The inhibitor data reported here stuggest that nucleic acid (mRNA) as well as protein synthesis are necessary for cyanidin biosynthesis in Sorghum.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The internal concentration at the site of action is n'ot known, but it is probably less than in the external solution. Factors of penetration and problems of degradation could also account for the higher concentrations required (26 (4,20) others implicate one of them in a role in gene activation (9). The inhibitor data reported here stuggest that nucleic acid (mRNA) as well as protein synthesis are necessary for cyanidin biosynthesis in Sorghum.…”
Section: Discussionmentioning
confidence: 68%
“…The inhibitor data reported here stuggest that nucleic acid (mRNA) as well as protein synthesis are necessary for cyanidin biosynthesis in Sorghum. If the photoreactions control specific enzyme syntheses (17), the varied limiting factors cited in anthocyanin biosynthesis (4,20,23,25) cotuld be explained on a common basis. But it is difficult as yet to differentiate between cause and effect, and more precise information awaits the demonstration of flavonoid biosynthesis from C, and C., prectursors in cell-free preparations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some points that are seldom mentioned when the data of the action spectroscopy studies are used in discussions 1 Research partially supported by a National Science Foundation Grant, PCM76-80932, to A. L. M.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, consider the differences in the spectral sensitivity of anthocyanin synthesis in young seedlings: BL2 is the only effective region in sorghum (2); BL and FR are about equally effective in mustard (17); FR is more effective than BL in turnip (13); and BL is more effective than FR in tomato (11). The causes of these differences are still poorly understood and are partly responsible for the state of uncertainty about the nature of the HIR photoreceptor (9, 15).There are some points that are seldom mentioned when the data of the action spectroscopy studies are used in discussions 1 Research partially supported by a National Science Foundation Grant, PCM76-80932, to A. L. M.2 Abbreviations: BCJ: incandescent lamps with an integral dark red filter, having a cut-off at about 650 nm; BL: blue; R: red; FR: far red; W: white; HIR: high irradiance response; P: total phytochrome = Pr + Pfr, TD: total duration of exposure.about the possible identity of the HIR photoreceptor. (a) The experimental conditions (length, irradiance and mode of application of the light treatments, temperature, age of the system) used in different studies vary quite widely, as shown by the short list given in Table I.…”
mentioning
confidence: 99%